Pengaruh Perceived Ease Of Use, Perceived Risk, Dan Perceived Usefullnes, Terhadap Behavioral Intention Melalui Attitude Toward Using To Mobile Banking (Brimo) Di Kota Jepara - Putri, Putri Rizki Yuliandini; Rifqy Roosdhani, Mohamad (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
This study aims to analyze the effect of perceived ease of use, perceived risk, and perceived usefulness on behavioral intention with attitude toward using as mediation on BRImo mobile banking users in Jepara City. The research method used is quantitative with purposive sampling of 137 respondents, and data was collected through an online questionnaire based on Google Form. Data analysis using SmartPLS software version 4.0. The results showed that perceived ease of use and perceived usefulness had a positive and significant effect on, while perceived risk did not have a significant effect on attitude toward using. Perceived ease of use and perceived risk had a positive effect on behavioral intention, while perceived usefulness did not have a significant effect on behavioral intention. Attitude toward using also had a significant positive effect on behavioral intention. In the mediation test, Attitude toward using only mediated the effect of perceived usefulness on behavioral intention marginally or could be interpreted as weak.